Hubungan Antara Pola Tidur Dengan Kesehatan Mental Pada Mahasiswa Keperawatan Di Pekanbaru - Roni Saputra; Risma Saputri (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Mental health is a condition where an individual is aware of their abilities, able to deal with life's stress, able to work productively, and able to contribute to the surrounding. Thus, it is important to maintain mental health, one of which is by maintaining sleep patterns. This study aims to determine whether there is a relationship between sleep patterns and mental health in nursing students in Pekanbaru. This type of research is quantitative research with a cross-sectional design. The study was conducted at the Nursing Study Program, Univrrab, Ikes Payung Negri, Muhammadiyah University of Riau. The research period was from February to March 2025. The population in the study were nursing students at Univrrab, Ikes Payung Negr, Muhammadiyah University of Riau totaling 157 people. The sampling technique in the study was total sampling so that the number of samples was 157 people. The data collection method used a questionnaire. The results of the study showed that the majority of nursing students in Pekanbaru were 21 years old (45.9%) and female (84.1%). Furthermore, of the 107 respondents who had sleep pattern disorders, the majority or 67 (62.6%) also had poor mental health, while of the 50 respondents who did not have sleep pattern disorders, the majority or 45 (90%) also had good mental health. Based on the chi square statistical test, a p value of 0.000 <0.05 was obtained. Thus, it is concluded that there is a real relationship between sleep patterns and mental health in nursing students in Pekanbaru. The odd ratio value of 15.075 means that students with sleep pattern disorders are 15.075 times more likely to have poor mental health. with a 95% confidence level, the incidence of poor mental health in the population ranges from 5,526-41,122.